Use the identity P(A ∪ B) = P(A)+P(B)-P(A ∩ B)
P(A)=0.50
P(B)=0.60
P(A ∪ B) = 0.30
=>
P(A ∪ B) = P(A)+P(B)-P(A ∩ B)
=(0.50+0.60)-0.30
=0.80
Answer:
-4.2, -3.5, -2.1, -1.5, -1, -0.5, 0.5, 3.5, 4.8
Step-by-step explanation:
Answer:
liner
Step-by-step explanation:
they look like a line on a graph
<span>-5n + 15 is the answer I think
I understand if it's not</span>
The correct answer would be 3 +/-
In order to solve for this you must first get the equation equal to 0.
x^2 + 6x + 9 - 6 ----> simplify like terms
x^2 + 6x + 3
Now knowing this we can use the coefficients of each one in descending order of power as a, b and c.
a = 1 (because it is the coefficient to x^2)
b = 6 (because it is the coefficient to x)
c = 3 (because it is the end number)
Now we can plug these values into the quadratic equation.
3 +/-
And those would be your two answers.